Mesomycoplasma hyopneumoniae lipoprotein Mhp390 serves as a plasminogen receptor mediating extracellular matrix degradation and respiratory epithelial cells injury - Wei Liu; Liying Ye; Keli Yang; Xingyu Yan; Ting Gao; Fangyan Yuan; Rui Guo; Zewen Liu; Chang Li; Qiong Wu; Jiajia Zhu; Yongxiang Tian; et al. (Veterinary Research)
Abstract The destruction of the respiratory barrier caused by Mesomycoplasma (Mycoplasma) hyopneumoniae plays a pivotal role in facilitating secondary infections by other respiratory pathogens. However, the pathogenesis of M. hyopneumoniae breaching the respiratory barrier to establish infection remains largely elusive. In this study, the role of Mhp390 encoded by M. hyopneumoniae in invasion of the respiratory tract barrier, including extracellular matrix and tracheal epithelial cells, were investigated through the Transwell assay. Our finding indicated that M. hyopneumoniae may exploit the host fibrinolytic system via Mhp390 to accumulate activated plasmin outside its membrane, thereby breaching the respiratory tract barrier and facilitating the progression of infection. Furthermore, the key functional domains within Mhp390 involved in its interaction with host plasminogen were determined by using truncated mutation techniques. Collectively, these findings will enhance our understanding of the mechanism underlying respiratory barrier invasion by M. hyopneumoniae thereby providing new theoretical basis for the development of novel vaccines and effective control strategies against secondary infection.